Wear-resistant epoxy resin composite material and preparation method thereof

Through modified dispersed filler and heat treatment technology, the bonding strength of epoxy resin composite materials at the phase separation boundary is improved, and the problem of insufficient wear resistance and load capacity is solved, and higher wear resistance and load capacity is achieved.

CN119661985APending Publication Date: 2025-03-21浙江巴顿焊接技术研究院 +3
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411935334.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing epoxy resin composite materials have low bonding strength, low wear resistance and overall low mechanical properties at the phase separation boundary.

Method used

The polymer based on epoxy resin binder is synthesized by modifying dispersed fillers and heat treatment is performed to increase the mutual adhesion of phase separation boundaries, form a polyvinyl alcohol transition layer and a plasticized polyethylene layer, and improve the wear resistance and load capacity of the composite material.

Benefits of technology

It significantly improves the wear resistance and load capacity of the composite material, reduces the friction coefficient, and extends the service life and load capacity of the friction unit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661985A_ABST
    Figure CN119661985A_ABST
Patent Text Reader

Abstract

The invention provides a wear-resistant epoxy resin composite material and a preparation method thereof, the wear-resistant epoxy resin composite material comprises an epoxy resin matrix material, and first particles and second particles dispersed in the epoxy resin matrix material, the first particles comprise mineral dispersion filler particles and polyvinyl alcohol transition layers wrapping the surfaces of the mineral dispersion filler particles; the second particles comprise dispersed polyethylene particles and plasticized polyethylene layers wrapping the surfaces of the dispersed polyethylene particles. According to the invention, a polymer based on the epoxy resin binder is synthesized in the form of modified dispersed filler, heat treatment is carried out, and the wear resistance and load capacity of the composite material are improved by increasing the mutual bonding effect of phase separation boundaries in an epoxy resin binder-dispersed filler system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of friction reduction and lubrication, and specifically relates to a wear-resistant epoxy resin composite material and a preparation method thereof. Background Art

[0002] Epoxy resin is a kind of artificially synthesized high molecular polymer, which is a viscous liquid or a solid that can be softened by heating. It usually has a melting or softening temperature range when heated, and can be in a plastic flow state under the action of external force; and epoxy resin has strong cohesion, dense molecular structure, and active unsaturated groups in the molecular structure, so that they can cross-link with various types of curing agents to form insoluble polymers with three-dimensional grid structures. After curing, epoxy resin has good physical and chemical properties, can also bond a variety of metal materials and non-metallic materials, has good dielectric properties, small set shrinkage, and high product dimensional stability. Therefore, it is widely used. However, in practical applications, pure epoxy resin materials have unsatisfactory wear resistance, which affects the service life of epoxy resin materials. Therefore, some people have modified epoxy resin materials. For example, a patent for a method for producing a polymer coating for protecting metal surfaces [Ukraine: UA63000], which continuously coats multiple layers of polymer materials on the steel surface to form a composite coating to improve the protective performance. The coating used includes a primer layer based on epoxy resin, a hot melt polymer intermediate layer based on ethylene copolymer and a protective layer based on extruded polyolefin. The hot melt polymer intermediate layer includes a thermoplastic adhesive based on ethylene and vinyl acetate copolymer, (meth) acrylic acid and / or (meth) acrylate, polyethylene and maleic anhydride graft copolymer, and an aromatic polycarbodiimide as a crosslinking catalyst. These components are molded on an epoxy resin material with a degree of curing ranging from 5% to 95%. The thermoplastic adhesive contains materials with active surface functional groups, so that the thermoplastic adhesive layer and the epoxy resin composite material layer have high bonding strength. The method completes the coating of each layer of the epoxy resin composite material through a rapid cooling process and completes the crosslinking of each layer. The thermoplastic adhesive containing the polycarbodiimide component is formed by a melt extrusion method. The coating formation process of this method is complicated and the process control is difficult, and the interlayer adhesion and water resistance at the phase separation boundary are low.

[0003] Patent: A method for manufacturing epoxy resin composite materials [Ukraine: UA127401], which is to form a mechanical mixture based on epoxy resin by combining the components in the form of dispersed fillers. Phthalimide is added to the polymer as a modifier, followed by heat treatment and additional treatment using a high-energy magnetic field. Finally, phytic acid and a curing agent are added, and the epoxy resin composite material of the desired shape is formed within 60 to 80 minutes. This method requires the use of magnetic processing equipment, the process is complicated, and the overall physical and mechanical properties of the epoxy resin composite material produced by this method are not high.

[0004] Patent: A method for producing epoxy resin materials for friction technology [Ukraine: UA101934], which is the closest to the present invention. The method uses a pressurized molding method to obtain a polymer according to the viscosity and application range of the material. The specific process is as follows: 1. Preparation and dosage adjustment of each component; 2. Adding a curing agent to the epoxy oligomer (the quantitative amount of the component is determined according to the stoichiometric ratio of the component); 3. The components in the polymer are combined by flow technology to achieve uniformity; 4. The polymer is vacuumed for 40-60 minutes; 5. Heat treatment; 6. Quality control of the formed polymer. When the components are combined by flow technology, they are subjected to additional ultrasonic and ultraviolet treatment; the heat treatment process is 0.5-1.5 hours at 60°C + 0.5-1.5 hours at 120°C + 1.0-2.0 hours at 200°C, and then cooled in still air. This heat treatment method can reduce the internal stress generated by the primary cross-linking unit, accelerate the structure formation process, and maximize the cross-linking degree of the system in the final stage. This method can be used to produce high-strength, wear-resistant materials in mechanical engineering, and to improve the physical, mechanical and friction properties of equipment operating under high-load sliding friction conditions. However, its friction coefficient is relatively high and its wear resistance is low, especially when the friction pair starts to resume sliding after stagnation, so it cannot be used in heavy-load friction devices. At the same time, the adhesion strength of the phase separation boundary formed by this method is low. Its heat treatment process, heat treatment at 200°C will cause the polymer to be damaged, thereby significantly reducing its load capacity. Cooling from 200°C in still air will cause high residual stress due to the fast cooling rate.

[0005] Therefore, how to enhance the mutual adhesion of phase separation boundaries in the system and improve the wear resistance and load capacity of composite materials is a current problem. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present application is to provide a wear-resistant epoxy resin composite material and a preparation method thereof, which is used to solve the problems of low bonding strength at the phase separation boundary, low wear resistance and overall low mechanical properties of the current epoxy resin composite material.

[0007] To solve the above problems, the technical solution adopted in this application is:

[0008] The present invention provides a wear-resistant epoxy resin composite material, which is characterized by comprising an epoxy resin matrix material and first particles and second particles dispersed in the epoxy resin matrix material, wherein the first particles comprise mineral dispersed filler particles and a polyvinyl alcohol transition layer wrapped on the surface of the mineral dispersed filler particles; and the second particles comprise dispersed polyethylene particles and a plasticized polyethylene layer wrapped on the surface of the dispersed polyethylene particles.

[0009] As a preferred embodiment of the present application, the polyvinyl alcohol transition layer is an interpenetrating polymer network formed by a polyvinyl alcohol solution layer wrapped on the surface of the mineral dispersed filler particles and an epoxy resin matrix material after heat treatment; the plasticized polyethylene layer is a plasticized polyethylene film made by heat treating the polyethylene on the surface of the dispersed polyethylene particles and the mineral oil layer wrapped on the surface of the dispersed polyethylene particles.

[0010] The present invention also provides a method for preparing the wear-resistant epoxy resin composite material, which is characterized by comprising the following steps:

[0011] Step 1: firstly mix a mineral dispersible filler with a polyvinyl alcohol solution, then add the mixture into an epoxy resin matrix material to obtain a treatment liquid A, and heat-treat the treatment liquid A to obtain an epoxy resin polymer containing first particles;

[0012] Step 2, dispersing mineral oil in dispersed polyethylene to form second particles before modification;

[0013] Step 3, dispersing the second particles before modification in the epoxy resin polymer containing the first particles to obtain a preliminary composite material;

[0014] Step 4, adding a curing agent to the primary composite material, stirring, molding, and curing to obtain a cured composite material;

[0015] Step 5: heat-treating the cured composite material to obtain a wear-resistant epoxy resin composite material containing the first particles and the second particles.

[0016] As a preferred embodiment of the present application, the epoxy resin matrix material is bisphenol A epoxy resin.

[0017] As a preference of the present application, the polyvinyl alcohol solution in step 1 is a polyvinyl alcohol aqueous solution with a mass concentration of 5 to 20% prepared in distilled water above its glass transition temperature (850° C.).

[0018] As a preference of the present application, the polyvinyl alcohol solution in step 1 is a polyvinyl alcohol aqueous solution with a mass concentration of 10% prepared in distilled water above its glass transition temperature.

[0019] As a preference of the present application, the mineral dispersing filler is a metal oxide.

[0020] As a preference of the present application, the mineral dispersing filler is selected from at least one of Cr2O3, Al2O3 and red mud.

[0021] As a preference of the present application, the mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is (1-5):(0.3-0.5):(1-5):10.

[0022] As a preference of the present application, the mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is (2-3):(0.3-0.5):(2-3):10.

[0023] As a preference of the present application, the mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is (2-2.5):(0.3-0.5):(2-3):10.

[0024] As a preference of the present application, the mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is 2.5:0.4:2:10.

[0025] As a preference of the present application, the volume mass ratio of mineral oil to polyethylene is (1-3):(2-3).

[0026] As a preference of the present application, the volume mass ratio of mineral oil to polyethylene is 2:(2-3).

[0027] As a preference of the present application, the volume mass ratio of mineral oil to polyethylene is 1:1.

[0028] As a preference of the present application, the particle size of the mineral dispersion filler is 20 to 60 μm.

[0029] As a preferred embodiment of the present application, the thickness of the coating layer is 100 to 250 μm, preferably 200 μm.

[0030] As a preference of the present application, the particle size of the dispersed polyethylene is 80 to 100 μm.

[0031] As a preference of the present application, the plasticized polyethylene layer has a thickness of 5 to 10 μm.

[0032] As a preference of the present application, the mineral oil is MS-20 aviation engine oil.

[0033] As a preferred embodiment of the present application, the curing method in step 4 is: -3MPa for 35-40 minutes and the polymer is cured for 24 hours or more. It is used to remove air inclusions that serve as stress concentration points of the material, which can improve the physical and mechanical properties of epoxy resin composites. If the vacuum time is less than 35 minutes, the complete removal of air and gas inclusions cannot be guaranteed. If the curing time is less than 24 hours, the maximum degree of gelation in the composite material cannot be completed, the degree of cross-linking of the material is reduced, and the load capacity of the wear-resistant composite material is reduced.

[0034] As a preferred embodiment of the present application, the heat treatment in step 1 includes:

[0035] The treated liquid A is kept at 110-120° C. for 35-40 minutes to obtain a mixture B; and

[0036] The treatment liquid B was cooled to 20°C at a cooling rate of 1°C / min.

[0037] As a preferred embodiment of the present application, the heat treatment temperature in step 1 is 115° C. and the heat preservation time is 38 minutes.

[0038] As a preferred embodiment of the present application, in step 4, the heat treatment process is divided into two stages: insulation and cooling. The insulation stage is divided into two stages. The first stage is insulation at 95-105°C for 65-70 min, and the second stage is insulation at 128-135°C for 125-130 min; the cooling stage is divided into two stages. The first stage is gradually cooled at a rate of 0.5°C / min, insulation is performed every 10°C for 18-20 min, and the second stage is cooled to 20°C at a rate of 1°C / min when the temperature reaches 80-85°C.

[0039] As a preference of the present application, the curing agent is polyethylene polyamine.

[0040] As a preferred embodiment of the present application, the amount of the curing agent added is 1-3% of the mass of the epoxy resin matrix material, and most preferably 2%.

[0041] As a preferred embodiment of the present application, in step 4, after adding the curing agent to the primary composite material, stirring, molding, curing and molding are performed, and the curing treatment is performed in the following manner:

[0042] Add curing agent to the primary composite material with all components mixed evenly and stir, put the composite material into the mold by free casting or pressure, and then -3 MPa for 35 to 40 minutes, and allow the composite material to stand and cure at room temperature for 24 hours or more.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) The present application synthesizes a polymer based on an epoxy resin binder in the form of a modified dispersed filler and performs a heat treatment, thereby increasing the mutual adhesion of the phase separation boundary in the "epoxy resin binder-dispersed filler" system, thereby improving the wear resistance and load capacity of the composite material.

[0045] (2) The mineral dispersed filler is mixed with the polyvinyl alcohol aqueous solution, and then added to the epoxy resin matrix to form a mechanical mixture, and the mixture is kept at 110-120°C for 35-40 minutes, and then cooled to 20°C. Through the above pretreatment, a polyvinyl alcohol transition layer of the interpenetrating polymer network (IPN) type can be formed between the dispersed filler and the epoxy resin binder, thereby increasing the adhesion to the surface of the mineral dispersed filler particles. At the same time, a uniform mineral oil layer is formed on the surface of the dispersed polyethylene particles, reducing the friction coefficient and thus improving its wear resistance. The temperature of the above heat treatment needs to be controlled at 110-120°C. If it is lower than 110°C, the solvent in the polyvinyl alcohol cannot be removed, affecting the formation of the polyvinyl alcohol transition layer. If it is higher than 120°C, aggregates will be formed at the phase separation boundary, increasing the stress concentration area in the composite material.

[0046] (3) The components are mixed evenly by combining flow technology and -3 MPa for 35-40 minutes and the polymer is cured for 24 hours, which will remove the air inclusions that serve as the stress concentration points of the material and improve the physical and mechanical properties of the epoxy resin composite material. If the vacuum time is less than 35 minutes, the complete removal of air and gas inclusions cannot be guaranteed. If the curing time is less than 24 hours, the maximum degree of gelation in the composite material cannot be completed, the cross-linking degree of the material is reduced, and the load capacity of the wear-resistant composite material is reduced.

[0047] (4) When the temperature is kept at 95-105°C for 65-70 minutes and at 128-135°C for 125-130 minutes, the polyethylene surface and the mineral grease are plasticized, which greatly reduces the temperature of the transfer film, thereby greatly reducing the friction coefficient and improving the wear resistance of the material. Among them, for keeping at 95-105°C for 65-70 minutes, below 95°C and the holding time is less than 65 minutes, the crosslinking degree of the adhesive in the composite material will not be significantly increased, and above 105°C and the holding time exceeds 65 minutes will reduce the rate of the relaxation process, thereby increasing the residual stress in the composite material. For keeping at 128-135°C for 125-130 minutes, below 128°C and the holding time is less than 125 minutes, the complete formation of the structure with the maximum crosslinking degree cannot be guaranteed.

[0048] (5) The cooling of the composite material is divided into two stages. In the first stage, the composite material is gradually cooled at a rate of 0.5℃ / min, and the temperature is kept every 10℃ for 18-20min. In the second stage, when the temperature reaches 80-85℃, it is cooled to 20℃ at a rate of 1℃ / min, and then the product is removed from the mold. The residual stress in the material will be significantly reduced, and the service life and load capacity of the friction unit will be increased. For the first stage, if the cooling rate is lower than 0.5℃ / min, the change rate of the macromolecular closed set of the epoxy resin binder will not help to reduce the residual stress in the material. If the cooling rate is higher than 0.5℃ / min, the residual stress will increase due to the reduced relaxation of the main chain of the macromolecule. For the second stage, if the cooling rate is higher than 1℃ / min and cooled to 20℃, the residual stress in the material will increase due to the formation of physical nodes during the cross-linking process of the matrix. After ensuring the specified cooling conditions, the product is removed from the mold at 20℃, which can significantly reduce the residual stress in the material. This will increase the service life, operational reliability and load capacity of the friction unit during the interaction of the friction surfaces. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 A flow chart of a method for processing an epoxy resin polymer comprising first particles in an embodiment of the present application.

[0050] Figure 2 Schematic diagram of the formation of the polyvinyl alcohol transition layer of the wear-resistant epoxy resin composite material of the present application.

[0051] Figure 3 Flow chart of the processing method of the wear-resistant epoxy resin composite material of the present application.

[0052] Figure 4 Schematic diagram of forming a plasticized polyethylene layer around dispersed polyethylene particles of the present application.

[0053] Figure 5 Structural diagram of the wear-resistant epoxy resin composite material containing first particles and second particles of the present application.

[0054] Figure 6 Schematic diagram of the friction surface structure of the grinding body and the plasticized polyethylene layer of the present application (the plasticized polyethylene layer at area A in the figure is transferred to the grinding surface of the grinding body; P is the force direction; the arrow represents the rotation direction of the grinding body). DETAILED DESCRIPTION

[0055] The following describes the implementation of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. The present application can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application.

[0056] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.

[0057] In addition, it should be understood that one or more method steps mentioned in this application do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in this application does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these two explicitly mentioned devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of implementation of this application. Changes or adjustments in their relative relationships shall also be regarded as the scope of implementation of this application without substantial changes in the technical content.

[0058] In the following embodiments of the present application, the main raw materials and reagents used are: the epoxy resin matrix material is bisphenol A epoxy resin ED-20 (SYD128), purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; polyvinyl alcohol is purchased from Jinan Century Tongda Chemical Co., Ltd.; the mineral oil is MS-20 aviation engine oil, purchased from Shenyang Teli Petrochemical Co., Ltd.; dispersed polyethylene is purchased from Shanghai Huayi Additive Co., Ltd.; polyethylene polyamine is purchased from Shanghai Jinjinle Industrial Co., Ltd.

[0059] The present application is further described below in conjunction with specific embodiments, but the protection scope of the present application is not limited thereto.

[0060] Example 1

[0061] Step 1, 25g of Cr2O3 with a particle size of 20-60μm is mixed with 40g of a polyvinyl alcohol solution with a mass concentration of 10% to prepare a mixture (the mass concentration of the mineral dispersible filler is 30wt%, and the mass concentration is expressed as the amount added per 100wt% of the epoxy resin matrix material), and then the mixture is added to 100g of the epoxy resin matrix material (specifically bisphenol A type epoxy resin ED-20 (SYD128)) to obtain a series of treatment liquids A, and the treatment liquid A is kept at 115°C for 35-40min to obtain a treatment liquid B; then the treatment liquid B is cooled to 20°C at a cooling rate of 1°C / min to obtain an epoxy resin polymer containing the first particles;

[0062] Step 2, 20 g of mineral oil (specifically MS-20 aviation engine oil) and 20 g of dispersed polyethylene with a particle size of 80 to 100 μm are mixed to form the second particles before modification;

[0063] Step 3, dispersing the second particles before modification in the epoxy resin polymer containing the first particles to obtain a preliminary composite material;

[0064] Step 4: Add 2g of polyethylene polyamine to the primary composite material and stir. The components in the primary composite material are combined with the curing agent by flow technology. After mixing evenly, the mixed material is placed into a mold by free casting or pressurization. -3 MPa for 38 min, and cured at room temperature (20-22°C) for 24 h to remove air inclusions, thereby obtaining a cured composite material;

[0065] Step 5, heat-treating the cured composite material, the heat-treating process is divided into two stages: heat preservation and cooling, wherein the heat preservation is divided into two stages, the first stage is heat preservation at 100°C for 68 minutes, and the second stage is heat preservation at 130°C for 127 minutes. The cooling is divided into two stages, the first stage is gradually cooled at a rate of 0.5°C / min, and the heat preservation is performed once every 10°C for 18 to 20 minutes. In the second stage, when the temperature reaches 80 to 85°C, it is cooled to 20°C at a rate of 1°C / min, and a wear-resistant epoxy resin composite material containing the first particles and the second particles is obtained.

[0066] The effectiveness of the wear-resistant epoxy resin composite material prepared in this embodiment was tested, and the specific testing method is as follows:

[0067] According to the standard method and the "shaft-partial bushing" scheme, the sliding speed V = 0.5m / s in the load range of 0.25-3.5MPa; according to the "shaft-partial bushing" scheme, the shaft diameter is 10mm in the load range of 12.5-30MPa. The wear resistance of the coating material is determined by the weight loss of the coating during wear with a steel wear part with a diameter of 40mm and a hardness of 45-50HRC. The surface roughness of the wear part is Ra = 0.32μm.

[0068] In the test plan, the practical efficiency of the preparation method described in this embodiment was tested. During the experiment, the thickness of the composite material coating was 0.2 mm and the sliding speed was 0.1 m / s. The test conditions were: at a constant temperature of 20°C, the friction pair loads were 12.5 MPa, 20 MPa, and 30 MPa; at a constant load of 20 MPa, the temperatures were 20°C, 100°C, and 160°C. During the test, the friction coefficient of the friction pair will decrease by 15-20% after running-in, from 0.12 to 0.08. A 5-10 μm plasticized polyethylene film will be formed to ensure the stable operation of the friction device. The test cycle is limited to 70×103 cycles, which is sufficient to meet the equipment operation until overhaul. At a constant temperature of 20℃, the stable working cycles corresponding to the friction pair loads of 12.5MPa, 20MPa, and 30MPa are 12×103 cycles, 70×103 cycles, and 3×103 cycles, respectively; under a constant load of 20MPa, the stable working cycles corresponding to the temperatures of 20℃, 100℃, and 160℃ are 12×103 cycles, 70×103 cycles, and 3×103 cycles, respectively.

[0069] The properties of the wear-resistant epoxy resin composite material were determined, and the test results are shown in Table 1.

[0070] Example 2

[0071] The difference between this embodiment and embodiment 1 is that the amount of the mineral dispersing filler used is different, that is, the amount of the mineral dispersing filler used is 10 g (mass concentration is 10 wt%), and the rest of the processes are exactly the same.

[0072] Example 3

[0073] The difference between this embodiment and embodiment 1 is that the amount of the mineral dispersing filler used is different, that is, the amount of the mineral dispersing filler used is 20 g (mass concentration is 20 wt%), and the rest of the processes are exactly the same.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that the amount of the mineral dispersing filler used is different, that is, the amount of the mineral dispersing filler used is 50 g (mass concentration is 50 wt%), and the rest of the processes are exactly the same.

[0076] Example 5

[0077] The difference between this embodiment and embodiment 1 is that the amount of dispersed polyethylene used is different, the amount of dispersed polyethylene used is 10g (mass concentration is 10wt%), and the rest of the processes are exactly the same.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that the amount of dispersed polyethylene used is different, that is, the amount of dispersed polyethylene used is 25 g (mass concentration is 25 wt%), and the other processes are exactly the same.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that the amount of dispersed polyethylene used is different, that is, the amount of dispersed polyethylene used is 30 g (mass concentration is 30 wt%), and the other processes are exactly the same.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that the amount of dispersed polyethylene used is different, that is, the amount of dispersed polyethylene used is 50 g (mass concentration is 50 wt%), and the other processes are exactly the same.

[0084] Example 9

[0085] The difference between this embodiment and embodiment 1 is that the heat treatment process in step 1 is different, the heat treatment temperature is 110° C., and the other processes are exactly the same.

[0086] Example 10

[0087] The difference between this embodiment and embodiment 1 is that the heat treatment process in step 1 is different, the heat treatment temperature is 120° C., and the other processes are exactly the same.

[0088] Embodiment 11

[0089] The difference between this embodiment and embodiment 1 is that the heat treatment process in step 5 is different. The first stage in the insulation stage is kept at 95°C for 65 minutes, and the second stage is kept at 128°C for 125 minutes; the temperature of the second stage in the cooling process is 80°C, and the rest of the processes are exactly the same.

[0090] Example 12

[0091] The difference between this embodiment and embodiment 1 is that the heat treatment process in step 5 is different. The first stage in the insulation stage is kept at 105°C for 70 minutes, and the second stage is kept at 135°C for 130 minutes; the temperature of the second stage in the cooling process is 85°C, and the rest of the processes are exactly the same.

[0092] Comparative Example 1

[0093] The difference between this comparative example and Example 1 is that the base material is different. The base material of this comparative example is replaced by epoxyfuran, and the other processes are exactly the same.

[0094] Comparative Example 2

[0095] The difference between this comparative example and Example 1 is that the first particles and the second particles are not added to the base material, that is, the preparation method is adaptively adjusted, and the rest of the processes are exactly the same.

[0096] Comparative Example 3

[0097] The difference between this comparative example and Example 1 is that the first particles are not added to the base material. The specific preparation method is as follows:

[0098] Step 1, 25g of Cr2O3 with a particle size of 20-60μm and 40g of a polyvinyl alcohol solution with a mass concentration of 10% are mixed to prepare a mixture (the mass concentration of the mineral dispersible filler is 25wt%, and the mass concentration is expressed as the amount added per 100wt% of the epoxy resin matrix material), and then the mixture is added to 100g of the epoxy resin matrix material (specifically bisphenol A type epoxy resin ED-20 (SYD128)) to obtain a series of treatment liquids A, and the treatment liquids A are respectively kept at 115°C for 38min to obtain treatment liquids B; and then the treatment liquid B is cooled to 20°C to obtain an epoxy resin polymer containing first particles;

[0099] Step 2: Add 2g of polyethylene polyamine to the epoxy resin polymer containing the first particles and stir. The components of the composite material are combined with the curing agent by flow technology. After mixing evenly, the mixed material is placed in a mold by free casting or pressurization. -3 MPa for 35 to 40 minutes, and then cured at room temperature (20 to 22°C) for 24 hours to remove air inclusions, thereby obtaining a cured composite material;

[0100] Step 3, heat-treating the cured composite material, the heat-treatment process is divided into two stages: heat preservation and cooling, wherein the heat preservation is divided into two stages, the first stage is heat preservation at 100°C for 68 minutes, and the second stage is heat preservation at 130°C for 127 minutes. The cooling is divided into two stages, the first stage is gradually cooled at a rate of 0.5°C / min, and the heat preservation is performed every 10°C for 18 to 20 minutes. In the second stage, when the temperature reaches 80 to 85°C, it is cooled to 20°C at a rate of 1°C / min, and a wear-resistant epoxy resin composite material containing the first particles and the second particles is obtained.

[0101] Comparative Example 4

[0102] The difference between this comparative example and Example 1 is that no second particles are added to the base material. The specific preparation method is as follows:

[0103] Step 1, 20 g of mineral oil (specifically MS-20 aviation engine oil) and 20 g of dispersed polyethylene with a particle size of 80 to 100 μm are mixed to form second particles before modification;

[0104] Step 2, dispersing the second particles before modification in the epoxy resin matrix material to obtain a primary composite material;

[0105] Step 3: Add 2g of polyethylene polyamine to the primary composite material and stir. The components in the primary composite material are combined with the curing agent by flow technology. After mixing evenly, the mixed material is placed into a mold by free casting or pressurization. -3 MPa for 35 to 40 minutes, and then cured at room temperature (20 to 22°C) for 24 hours to remove air inclusions, thereby obtaining a cured composite material;

[0106] Step 4, heat-treating the cured composite material, the heat-treating process is divided into two stages: heat preservation and cooling, wherein the heat preservation is divided into two stages, the first stage is heat preservation at 100°C for 68 minutes, and the second stage is heat preservation at 130°C for 127 minutes. The cooling is divided into two stages, the first stage is gradually cooled at a rate of 0.5°C / min, and the heat preservation is performed once every 10°C for 18 to 20 minutes. In the second stage, when the temperature reaches 80 to 85°C, it is cooled to 20°C at a rate of 1°C / min, and a wear-resistant epoxy resin composite material containing the first particles and the second particles is obtained.

[0107] Comparative Example 5

[0108] The difference between this comparative example and Example 1 is that the treatment liquid A is not subjected to heat treatment in step 1, and the rest of the processes are exactly the same.

[0109] Comparative Example 6

[0110] The difference between this comparative example and Example 1 is that step 5 adopts the same heat treatment as step 1, and the other processes are exactly the same.

[0111] The performance test methods and results of the composite materials prepared in Examples 2 to 12 and Comparative Examples 1 to 8 are equivalent to those in Example 1, and will not be described in detail herein.

[0112] Table 1

[0113]

[0114] As can be seen from the above table, the base materials in Examples 1 to 12 and Comparative Examples 2 to 6 are all bisphenol A epoxy resin ED-20 (SYD128), and the polymer uses polyethylene polyamine as a curing agent, which can make the composite material molded at room temperature, while Comparative Example 1 and Comparative Example 7 cannot be molded at room temperature. In Examples 1 to 8, the mineral dispersing filler uses a high modulus mineral dispersing filler (such as metal oxides Cr2O3, Al2O3, red mud, etc., and Cr2O3 is used as an example in this application) as a dispersing filler to improve the overall elastic modulus of the composite material, and the mass concentration of the mineral dispersing filler is preferably 10 to 50wt%, more preferably 20 to 25wt%, and optimally 25wt%, and the dispersing filler dispersion is 20 to 60μm; the mass concentration of the dispersed polyethylene is preferably 10 to 50wt%, more preferably 20 to 30wt%, and optimally 20wt%, and the dispersing filler dispersion is 80 to 100μm. In the matrix material, adding 20, 25, 30wt% of dispersed polyethylene per 100wt% (the component concentrations below are expressed as added per 100wt% of the matrix) can increase the wear resistance by 8 to 10 times. Adding plasticized polyethylene (plasticized separately from the matrix with MS-20 mineral oil) can reduce the degree of wear by 90 to 92%. Adding polyethylene and mineral oil to the matrix and heat treating the material can further improve the wear resistance. At the same time, it can be observed that the friction pair temperature drops from 90 to 108°C to 40 to 42°C. By comparing the performance of two different matrixes, epoxy resin as the matrix has a better effect in terms of friction pair temperature change, wear resistance and load capacity. By conducting friction tests under different loads, the results show that the epoxy resin composite material containing 20wt% polyethylene and 25wt% mineral dispersed filler has high wear resistance. According to the production method of the present invention, the composite material has a load capacity of up to 3.5MPa and a friction coefficient of 0.12.

[0115] It can be seen from Example 1 that the curing time needs to reach 24 hours or more, which will remove the air inclusions that serve as the stress concentration point of the material and improve the physical and mechanical properties of the epoxy resin composite material. If the vacuum time is less than 35 minutes, the complete removal of air and gas inclusions cannot be guaranteed. If the curing time is less than 24 hours, the maximum gelation in the composite material cannot be completed, the cross-linking degree of the material is reduced, and the load capacity of the wear-resistant composite material is reduced. In addition, it should be noted that the polyvinyl alcohol solution needs to be prepared in distilled water above its glass transition temperature (850°C) and mixed with a mineral dispersion filler at this temperature, which can improve the diffusion process at the phase separation boundary. The epoxy resin matrix material is then added and homogenized using flow technology. To remove the solvent in the polymer, heat treatment is carried out at a temperature of 110-120°C for 35-40 minutes. PVA will form a thin film with strong adhesion on the surface of the dispersed filler, namely the polyvinyl alcohol transition layer. The transition layer is an interpenetrating polymer network (IPN) formed between the mineral dispersed filler particles and the epoxy resin matrix material. This structure can significantly increase the mutual adhesion of the phase separation boundary. Under this condition, due to the pores (mechanical bite) and the physical nodes formed with polyvinyl alcohol, PVA is well combined with the epoxy resin matrix, thereby improving the wear resistance and load capacity of the composite material.

[0116] Compared with Example 11 and Example 12, it can be seen that the heat treatment process of the composite material after curing in step 5 is divided into two stages. In the first stage, the heat treatment is carried out at 95-105°C for 65-70min. In this stage, the polyethylene is plasticized, the crosslinking degree of the epoxy resin matrix increases, and the residual stress in the polymer is relaxed. In the second stage, the heat treatment is carried out at 128-135°C for 125-130min. Under this condition, the additional crosslinking of the epoxy resin matrix is ​​increased by increasing the fluidity of the adhesive macromolecules. At the same time, the physical nodes between the adhesive macromolecules are destroyed, the fluidity of the macromolecules is increased, and a network structure is finally formed. For heat treatment at 95-105°C for 65-70min, below 95°C and the heat treatment time is less than 65min, the crosslinking degree of the adhesive in the composite material will not be significantly increased. Above 105°C and the heat treatment time exceeds 65min, the rate of the relaxation process will be reduced, thereby increasing the residual stress in the composite material. For the incubation at 128-135°C for 125-130 min, below 128°C and for a incubation time of less than 125 min, the complete formation of the structure with the maximum cross-linking degree cannot be guaranteed.

[0117] The cooling of the composite material is divided into two stages. In the first stage, it is gradually cooled at a rate of 0.5℃ / min, and the temperature is kept every 10℃ for 18-20min. Under this condition, the epoxy resin macromolecules have additional interactions with PVA, and the high fluidity of the polyvinyl alcohol macromolecules is conducive to the relaxation of the residual stress at the phase separation boundary, which significantly reduces the overall residual stress of the composite material. In the second stage, when the temperature reaches 80-85℃, it is cooled to 20℃ at a rate of 1℃ / min, and then the product is removed from the mold. Under this condition, the residual stress in the composite material will not change much. For the first stage, if the cooling rate is lower than 0.5℃ / min, the change rate of the closed set of epoxy resin binder macromolecules will not help to reduce the residual stress in the material. If the cooling rate is higher than 0.5℃ / min, the residual stress will increase due to the reduced relaxation of the main chain of the macromolecule. For the second stage, if the cooling rate is higher than 1℃ / min and cooled to 20℃, the residual stress in the material will increase due to the formation of physical nodes during the cross-linking process of the matrix. After ensuring the specified cooling conditions, removing the product from the mold at 20°C significantly reduces the residual stress in the material. This increases the service life, operational reliability and load capacity of the friction unit during the interaction of the friction surfaces.

[0118] In addition, under a constant load of 20MPa, the temperature is 20℃, 100℃, and 160℃. During the test, the friction coefficient of the friction pair will decrease by 15-20% after running-in, from 0.12 to 0.08. A 5-10μm plasticized polyethylene film will be formed to ensure the stable operation of the friction device.

[0119] In summary, the present invention synthesizes a polymer based on an epoxy resin binder in the form of a modified dispersed filler and performs a heat treatment, thereby increasing the mutual adhesion of the phase separation boundary in the "epoxy resin binder-dispersed filler" system, thereby improving the wear resistance and load capacity of the composite material.

[0120] The above examples are for the purpose of illustrating the embodiments disclosed in the present application and should not be construed as limiting the present application. In addition, the various modifications listed herein and the variations of methods and compositions in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present application. Although the present application has been specifically described in conjunction with various specific preferred embodiments of the present application, it should be understood that the present application should not be limited to these specific embodiments. In fact, various modifications obvious to those skilled in the art as described above to obtain inventions should be included within the scope of the present application.

Claims

1. A wear-resistant epoxy resin composite material, characterized in that: It includes an epoxy resin matrix material and first particles and second particles dispersed in the epoxy resin matrix material. The first particles include mineral dispersed filler particles and a polyvinyl alcohol transition layer wrapped on the surface of the mineral dispersed filler particles; the second particles include dispersed polyethylene particles and a plasticized polyethylene layer wrapped on the surface of the dispersed polyethylene particles.

2. The wear-resistant epoxy resin composite material according to claim 1, characterized in that: The polyvinyl alcohol transition layer is an interpenetrating polymer network formed by a polyvinyl alcohol solution layer wrapped on the surface of mineral dispersed filler particles and an epoxy resin matrix material after heat treatment; the plasticized polyethylene layer is a plasticized polyethylene film made by heat treating the polyethylene on the surface of the dispersed polyethylene particles and the mineral oil layer wrapped on the surface of the dispersed polyethylene particles.

3. A method for preparing the wear-resistant epoxy resin composite material according to claim 2, characterized in that: The following steps are involved: Step 1: firstly mix a mineral dispersible filler with a polyvinyl alcohol solution, then add the mixture into an epoxy resin matrix material to obtain a treatment liquid A, and heat-treat the treatment liquid A to obtain an epoxy resin polymer containing first particles; Step 2, dispersing mineral oil in dispersed polyethylene to form second particles before modification; Step 3, dispersing the second particles before modification in the epoxy resin polymer containing the first particles to obtain a preliminary composite material; Step 4, adding a curing agent to the primary composite material, stirring, molding, and curing to obtain a cured composite material; Step 5: heat-treating the cured composite material to obtain a wear-resistant epoxy resin composite material containing the first particles and the second particles.

4. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The polyvinyl alcohol solution in step 1 is a polyvinyl alcohol aqueous solution with a mass concentration of 5-20% prepared in distilled water above its glass transition temperature.

5. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is (1-5): (0.3-0.5): (1~5):10。 6. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is (2-3): (0.3-0.5): (2~3):10。 7. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The mass ratio of the mineral dispersed filler, polyvinyl alcohol, dispersed polyethylene and epoxy resin matrix material is 2.5:0.4:2:

10.

8. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The heat treatment in step 1 includes: The treatment liquid A is kept at 110-120° C. for 35-40 minutes to obtain the treatment liquid B; and The treatment liquid B was cooled to 20°C at a cooling rate of 1°C / min.

9. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: In step 5, the heat treatment process is divided into two stages: insulation and cooling. The insulation stage is divided into two stages. The first stage is insulation at 95-105°C for 65-70min, and the second stage is insulation at 128-135°C for 125-130min; the cooling stage is divided into two stages. The first stage is gradually cooled at a rate of 0.5°C / min, insulation is performed every 10°C for 18-20min, and the second stage is cooled to 20°C at a rate of 1°C / min when the temperature reaches 80-85°C.

10. The method for preparing the wear-resistant epoxy resin composite material according to claim 3, characterized in that: The curing agent is polyethylene polyamine.

Citation Information

Patent Citations

  • Method and unit for the production of granulated carbamide

    UA101934C2

  • Antineoplastic composition comprising synergetic combination of anthracyclin and camptotecin derivatives

    UA63000C2

  • Wear resistant layer

    CN111511485A

  • Preparation method of high-wear-resistance epoxy resin-silicon carbide composite material

    CN116496606A

  • High-hydrophobicity wear-resistant heavy-duty anti-corrosion coating material as well as preparation method and application thereof

    CN117551376A